Optimizing Spawn Production and Yield of Shiitake Mushroom (Lentinula edodes) - A Comprehensive Study on Grain Substrates and Growth Supplements - Shanmugaraj, C.; Saranraj, K.; Biswas, M. K. (International Journal of Economic Plants, 2025)
The experiment was conducted during January to June, 2023 at the Mushroom Research Laboratory, Department of Plant Pathology, Palli Siksha Bhavana, Visva-Bharati University, West Bengal, India, focused on assessing various substrates and supplements for optimizing the cultivation of Lentinula edodes (Shiitake mushrooms). Analysis of spawn run durations across different grain substrates revealed sorghum as the most efficient, with strain LE-03 exhibiting the fastest colonization in just 13.67 days. Paddy and wheat substrates followed suit, while maize exhibited the longest colonization times across all strains. Rice bran emerged as the most efficient treatment for spawn run duration, surpassing wheat bran and groundnut oil cake, with the control group requiring the longest duration. Furthermore, examination of supplements highlighted wheat bran as consistently yielding the highest mushroom weight (750 grams of substrate-1) and biological efficiency (46.48% to 54.71%) across all strains. Rice bran also showed competitive results, particularly in yield. Groundnut oil cake consistently lagged behind in both yield and biological efficiency compared to wheat and rice bran, while the control group consistently produced the lowest results. These findings underscore the importance of substrate and supplement selection in optimizing spawn run duration, yield, and biological efficiency in Shiitake mushroom cultivation. Wheat bran and rice bran emerged as superior supplements, maximizing both yield and biological efficiency, while groundnut oil cake and the control group exhibited comparatively inferior performance. This comprehensive analysis provides valuable insights for enhancing Shiitake mushroom cultivation practices, emphasizing the significance of substrate and supplement choices for achieving optimal results.